PROFESIONALISME MAHASISWA AKUNTANSI DAN MAHASISWA ADMINISTRASI BISNIS DALAM MENGOPERASIKAN APLIKASI KOMPUTER AKUNTANSI - Suharyono, Suharyono (Widya Mandala Surabaya Catholic University, 2019)
The decision of the Minister of Manpower and Transmigration Number 182 of 2013 concerning the Establishment of Indonesian National Work Competency Standardsstates that one of the competency units that accountants must possess is operating an accounting computer application. This research was conducted to prove and compare the results of competency tests, especially the units operating accounting computer applications between students of the Accounting Department and the Business Administration Department. The test tool used was the Mann-Whitney nonparametric test. The sample in this study amounted to 104 students, consisting of 52 Accounting Department students and 52 Business Administration students. The results of this study indicate that the competence to operate accounting computer applications between students of the Accounting Department and Business Administration Department has a significant difference